Faktor – Faktor Yang Mempengaruhi Nilai Perusahaan Padaperusahaan Manufaktur Yang Terdaftar Di Bei - Fiolin Alfaro, Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study aims to determine how much influence dividend policy, intellectual capital, and firm growth to determine the firm value. The population in this study are manufacturing companies listed in Indonesia Stock Exchange (BEI) period 2015-2017. With used purposive sampling method and selected 33 companies. The data used in this study is secondary data. Data collection technique with technique of documentation. Analysis of research is using multiple regression analysis. The result of this study indicated dividend policy have positive effect and no significant on firm value, intellectual capital have positive effect and significant on firm value, and firm growth have negative effect and no significant on firm value.